3D S-wave velocity structure of the Ningdu basin in Jiangxi province inferred from ambient noise tomography with dense array - Long Teng; Xiangteng Wang; Chunlei Fu; Feng Bao; Jiajun Chong; Sidao Ni; Zhiwei Li (Earthquake Research Advances, 2023)
The Ningdu basin, located in southern Jiangxi province of southwest China, is one of the Mesozoic basin groups which has exploration prospects for geothermal energy. A study on the detailed velocity structure of the Ningdu basin can provide important information for geothermal resource exploration. In this study, we deployed a dense seismic array in the Ningdu basin to investigate the 3D velocity structure and discuss implications for geothermal exploration and geological evolution. Based on the dense seismic array including 35 short-period (5 s-100 ​Hz) seismometers with an average interstation distance of ∼5 ​km, Rayleigh surface wave dispersion curves were extracted from the continuous ambient noise data for surface wave tomographic inversion. Group velocity tomography was conducted and the 3D S-wave velocity structure was inverted by the neighborhood algorithm. The results revealed obvious low-velocity anomalies in the center of the basin, consistent with the low-velocity Cretaceous sedimentary rocks. The basement and basin-controlling fault can also be depicted by the S-wave velocity anomalies. The obvious seismic interface is about 2 ​km depth in the basin center and decreases to 700 ​m depth near the basin boundary, suggesting spatial thickness variations of the Cretaceous sediment. The fault features of the S-wave velocity profile coincide with the geological cognition of the western boundary basin-controlling fault, which may provide possible upwelling channels for geothermal fluid. This study suggests that seismic tomography with a dense array is an effective method and can play an important role in the detailed investigations of sedimentary basins.